A method for preparing a fly ash-polydopamine ceramic membrane for oil-water separation
Patent Information
- Application Number
- CN202511269929.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-08
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2045-09-08
AI Technical Summary
但存在两大技术瓶颈,(1)粉煤灰含未燃碳及金属杂质,直接烧结易导致膜结构缺陷;(2)粉煤灰基膜表面亲水性不足,处理水包油乳液时通量衰减快
[0018](1)本发明通过聚多巴胺表面改性,在粉煤灰陶瓷膜界面构建亲水-荷电双效功能层,协同实现高孔隙率贯通孔道与高通量特性,显著提升油水分离截留率>95%并强化抗污染稳定性;
Smart Images

Figure CN121177976B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic membrane technology, and specifically relates to a method for preparing a fly ash-polydopamine ceramic membrane for oil-water separation. Background Technology
[0002] Ceramic membranes have significant advantages in the treatment of oily wastewater due to their excellent mechanical strength and chemical stability. However, traditional alumina / zirconia ceramic membranes are 5-8 times more expensive than organic membranes because of their high raw material costs and high sintering energy consumption (>1000℃). Fly ash, as an aluminum- and silicon-rich solid waste, has the potential to replace traditional ceramic raw materials and reduce costs. However, there are two major technical bottlenecks: (1) Fly ash contains unburned carbon and metal impurities, which can easily lead to membrane structure defects when directly sintered; (2) The surface of fly ash-based membranes is not hydrophilic enough, resulting in rapid flux decay when treating oil-in-water emulsions.
[0003] Existing modification techniques (such as plasma treatment and silane coupling agent modification) suffer from complex processes or poor stability, making them difficult to industrialize. Polydopamine (PDA) is an ideal modifier due to its strong adhesion and hydrophilic groups; however, there is still a lack of effective methods to achieve uniform loading of PDA within the pores of fly ash ceramic membranes. Therefore, a method for preparing fly ash-polydopamine ceramic membranes for oil-water separation is needed. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing a fly ash-polydopamine ceramic membrane for oil-water separation.
[0005] This invention includes the following steps:
[0006] S1 involves alkaline washing and acid washing of fly ash to obtain pretreated fly ash;
[0007] S2 mixes the pretreated fly ash with polyvinylpyrrolidone (PVP), N-methylpyrrolidone (NMP) and polyethersulfone (PES) in a mass ratio of 60:2:80:20, adds distilled water, and then ball-mills the mixture in a planetary mill for 24 hours to obtain a slurry with a solid content of 50wt%.
[0008] S3 The slurry is shaped by a wet-dry spinning device, and the shaped slurry is placed in the external exchange liquid for phase inversion to obtain a ceramic membrane fiber preform; the preform is then subjected to gradient sintering to obtain a fly ash ceramic membrane support.
[0009] S4 The fly ash ceramic membrane support is vertically immersed in the modified alkaline solution, vacuumed for 10-20 minutes, and then transferred to a rotating device with a speed of 30 r / min for 10-15 minutes.
[0010] The fly ash ceramic membrane support after S5 treatment was dried in a 55℃ constant temperature oven for 10-12 minutes to obtain polydopamine modified fly ash ceramic membrane.
[0011] Furthermore, the alkaline washing solution used is a 2-4 wt% sodium hydroxide solution or a 15-25 wt% sodium carbonate solution, and the solid-liquid ratio of the alkaline washing is 1 kg:1.5 L to 1 kg:3 L.
[0012] Furthermore, the pickling solution used is a 1-3 wt% citric acid solution, a 3-7 wt% hydrochloric acid solution, a 1-5 wt% sulfuric acid solution, or a 0.5-3 wt% nitric acid solution, and the pickling solid-liquid ratio is 1 kg:0.5 L to 1 kg:2.5 L;
[0013] Furthermore, the shaping pressure is set to 0.15 MPa, the inner core liquid is deionized water with a flow rate of 80 mL / min, the outer exchange liquid is anhydrous ethanol and deionized water in a volume ratio of 4:6, and the spinning pressure is 0.15 MPa.
[0014] Furthermore, the gradient sintering process includes three stages: the first stage: 0℃-200℃, with a rate of 2-5℃ / min; holding for 80min; the second stage: 200℃-600℃, with a rate of 2-5℃ / min; holding for 170min; and the third stage: 600℃-1100℃, with a rate of 3-5℃ / min; holding for 122min.
[0015] Furthermore, the modified alkaline solution is based on Tris-HCl buffer solution, with the pH adjusted to 8.5-9, and dopamine hydrochloride is added to form the modified solution.
[0016] On the other hand, a fly ash-polydopamine ceramic membrane for oil-water separation is prepared by the aforementioned preparation method; the pore size of the ceramic membrane is 0.49 μm-2.24 μm.
[0017] Compared with the prior art, the present invention has the following advantages:
[0018] (1) This invention constructs a hydrophilic-charged dual-functional layer at the interface of fly ash ceramic membrane by modifying the surface of polydopamine, which synergistically achieves high porosity through channels and high throughput characteristics, significantly improves the oil-water separation retention rate >95% and enhances the anti-fouling stability.
[0019] (2) This invention effectively solves the problem of uniform loading of PDA in the complex pores of fly ash ceramic membrane. Vacuum assistance ensures that the modified alkali solution fully penetrates into the deep pores. Rotation treatment promotes its uniform distribution and reaction in the pores and on the membrane surface, avoiding local accumulation or incomplete coverage, and is easy to achieve large-scale production. Attached Figure Description
[0020] Figure 1 A comparison chart of fly ash particle sizes at different ball milling times;
[0021] Figure (a) shows the particle size distribution after 24 hours of ball milling, and Figure (b) shows the particle size distribution after 48 hours of ball milling.
[0022] Figure 2 This is a comparison chart of oil retention rates before and after modification in the preparation method of the fly ash-polydopamine ceramic membrane for oil-water separation according to the present invention.
[0023] Figure 3 This is a comparison chart of water flux before and after modification in the preparation method of the fly ash-polydopamine ceramic membrane for oil-water separation according to the present invention.
[0024] Figure 4 The images show surface (ac) and local cross-sectional (df) images of the fly ash ceramic membrane in different states (green, before modification, after modification) of the fly ash-polydopamine ceramic membrane for oil-water separation according to the preparation method of the present invention.
[0025] Figure 5 The image shows a comparison of the water contact angles of the fly ash ceramic membrane before and after modification, which is part of the preparation method of the fly ash-polydopamine ceramic membrane for oil-water separation according to the present invention. Detailed Implementation
[0026] The technical solution of the present invention will be further described below with reference to embodiments and comparative examples, but it should not be construed as a limitation of the present invention:
[0027] The technical solutions in some embodiments of this disclosure will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this disclosure, and not all embodiments. Based on the embodiments provided in this disclosure, all other embodiments obtained by those skilled in the art are within the scope of protection of this disclosure.
[0028] Example
[0029] Specific implementation method: The composition of the fly ash raw material used in this invention was determined by X-ray fluorescence spectrometry (XRF), and its key components are: Al2O3: 24.278%, SiO2: 46.025%, Fe2O3: 15.466%.
[0030] Example 1:
[0031] Technical objective: To solve the problems of uneven distribution of modified liquid inside membrane pores and insufficient enrichment on the surface by increasing the concentration of dopamine hydrochloride and extending the vacuum suction time; and to enhance the diffusion of modified liquid into deep pores by utilizing the extended vacuum permeation.
[0032] Pretreatment of fly ash:
[0033] Alkaline washing for impurity removal: Place fly ash in a 3-4 wt.% NaOH solution (solid-liquid mass ratio 1:3) and stir at 80℃ for 2 hours to oxidize and remove unburned carbon (residual carbon content <1 wt.%); Water washing and neutralization: Wash with deionized water until neutral (pH = 7 ± 0.5); Acid washing and purification: Place the alkaline-washed fly ash in a 4-6 wt.% HCl solution (solid-liquid mass ratio 1:2.5) and stir at room temperature for 1 hour to selectively dissolve dense-damaging components such as Fe2O3 and CaO; Secondary water washing: Wash with deionized water until neutral; Drying and grinding: Dry the washed fly ash in a 55℃ oven for 2-3 days and grind it into granules; Wet ball milling: Add distilled water and place in a planetary ball mill for 48 hours. After completion, transfer to a 55℃ oven to dry for 3-4 days to obtain fly ash with a particle size ≤6μm.
[0034] Preparation of ceramic membrane support:
[0035] Pretreated fly ash was mixed with polyvinylpyrrolidone (PVP), polyethersulfone (PES), and N-methylpyrrolidone (NMP) in a mass ratio of 60:2:20:80. After adding 10 mL of distilled water, the mixture was ball-milled for 24 hours to obtain a slurry with a solid content of 50 wt.%. The slurry was poured into a laboratory-made spinning device and extruded at a pressure of 0.15 MPa. The core liquid (deionized water) flow rate was 80 mL / min. The mixture was then placed in a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water = 4:6) for further processing. Phase inversion was performed, with the liquid level 15 cm above the discharge port, resulting in a fiber preform. After controlled-humidity drying, a fly ash ceramic membrane green body was obtained. The green body was then subjected to gradient sintering: first stage (0℃-200℃, rate: 2-5℃ / min, holding time 80 min); second stage (200℃-600℃, rate: 2-5℃ / min, holding time 170 min); third stage (600℃-1100℃, rate: 3-5℃ / min, holding time 122 min). After sintering, the green body was naturally cooled to obtain a fly ash ceramic membrane support.
[0036] Polydopa modified solution
[0037] Dissolve 0.121 g of tris(hydroxymethyl)aminomethane (Tris) in 40 mL of deionized water, add 2.5 mL of 0.1 mol / L hydrochloric acid (precisely adjust pH to 8.5), and bring the volume to 50 mL. Add 150 mg of dopamine hydrochloride (Tris: dopamine hydrochloride: HCl mass ratio = 121:150:9), stir to dissolve, and prepare a modified alkaline solution. Place the modified alkaline solution system containing the ceramic membrane support into a circulating water multi-purpose vacuum pump and evacuate for 20 min to allow the modified alkaline solution to be delivered to the pores of the fly ash ceramic membrane and the covering surface. Transfer the fly ash ceramic membrane to a rotating device and rotate (30 r / min) for 15 min. Place the rotated fly ash ceramic membrane in a 55℃ constant temperature oven and dry for 12 minutes to obtain a hydrophilic fly ash-polydopamine ceramic membrane.
[0038] Performance testing
[0039] The osmotic flux was determined using a self-made pressure osmosis apparatus in the laboratory. The osmotic flux (J, L·m) -2 ·h -1 The calculation formula is as follows: Where V is the permeate volume (L) over a certain period of time, and A is the effective membrane filtration area (m²). 2 ), where Δt is the test time (h).
[0040] The oil content in oil-water emulsions was analyzed using a UV-Vis spectrophotometer. The principle is based on the UV absorption characteristics of the -CH=CH- and -C6H5 groups in oils, and the fact that absorbance is directly proportional to the oil concentration in the solution. By plotting a standard curve and comparing the changes in absorbance before and after the standard curve, the oil content in the actual permeable side sample can be calculated, thus yielding the oil rejection rate. The oil rejection rate (R, %) is calculated using the following formula:
[0041] C f and C p The oil concentrations (mg·L) in the feed liquid and permeate are respectively. -1 ).
[0042] Technical effect: Permeation flux: 14892 L·m -2 ·h -1 The oil rejection rate was 95.2%, which is 31% higher than that of the unmodified fly ash ceramic membrane.
[0043] Example 2:
[0044] Extending the rotation treatment time (10 min → 15 min) promotes the smooth spreading of the surface modification liquid.
[0045] Pretreatment of fly ash:
[0046] Alkaline washing for impurity removal: Place fly ash in a 3-4 wt.% NaOH solution (solid-liquid mass ratio 1:3) and stir at 80℃ for 2 hours to oxidize and remove unburned carbon (residual carbon content <1 wt.%); Water washing and neutralization: Wash with deionized water until neutral (pH = 7 ± 0.5); Acid washing and purification: Place the alkaline-washed fly ash in a 4-6 wt.% HCl solution (solid-liquid mass ratio 1:2.5) and stir at room temperature for 1 hour to selectively dissolve dense-damaging components such as Fe2O3 and CaO; Secondary water washing: Wash with deionized water until neutral; Drying and grinding: Dry the washed fly ash in a 55℃ oven for 2-3 days and grind it into granules; Wet ball milling: Add distilled water and place in a planetary ball mill for 48 hours. After completion, transfer to a 55℃ oven to dry for 3-4 days to obtain fly ash with a particle size ≤6μm.
[0047] Preparation of ceramic membrane support:
[0048] Pretreated fly ash was mixed with polyvinylpyrrolidone (PVP), polyethersulfone (PES), and N-methylpyrrolidone (NMP) at a mass ratio of 60:2:20:80. After adding 10 mL of distilled water, the mixture was ball-milled for 24 hours to obtain a slurry with a solid content of 50 wt.%. The slurry was poured into a laboratory-made spinning device and extruded at a pressure of 0.15 MPa. The core liquid (deionized water) flow rate was 80 mL / min. The mixture was then placed in a mixed solution of anhydrous ethanol and deionized water (volume ratio of anhydrous ethanol to deionized water = 4:6) for further processing. Phase inversion was performed, with the liquid level 15 cm above the discharge port, resulting in a fiber preform. After controlled-humidity drying, a fly ash ceramic membrane green body was obtained. The green body was then subjected to gradient sintering: first stage (0℃-200℃, rate: 2-5℃ / min, holding time 80 min); second stage (200℃→600℃, rate: 2-5℃ / min, holding time 170 min); third stage (600℃→1100℃, rate: 3-5℃ / min, holding time 122 min). After sintering, the green body was naturally cooled to obtain the fly ash ceramic membrane.
[0049] Polydopa modified solution
[0050] Dissolve 0.121 g of tris(hydroxymethyl)aminomethane (Tris) in 40 mL of deionized water, add 2.5 mL of 0.1 mol / L hydrochloric acid (precisely adjust pH to 8.5), and bring the volume to 50 mL. Add 100 mg of dopamine hydrochloride (Tris: dopamine hydrochloride: HCl mass ratio = 121:100:9), stir to dissolve, and prepare a modified alkaline solution. Place the modified alkaline solution system containing the ceramic membrane support into a circulating water multi-purpose vacuum pump and evacuate for 10 min to allow the modified alkaline solution to be delivered into the pores of the fly ash ceramic membrane and onto the covering surface. Transfer the fly ash ceramic membrane to a rotating device and rotate (30 r / min) for 15 min. Place the rotated fly ash ceramic membrane in a 55℃ constant temperature oven and dry for 12 minutes to obtain a hydrophilic fly ash-polydopamine ceramic membrane.
[0051] like Figure 1 As shown in Figure a, fly ash has a wide particle size distribution, with some coarse particles >6μm. When the cumulative proportion reaches 100%, the corresponding particle size is approximately 8-10μm, indicating poor particle uniformity. Figure 1 As shown in b, the fly ash particle size is significantly refined and the distribution is concentrated, with more than 95% of the particles having a particle size ≤6μm. When the cumulative fraction reaches 100%, the corresponding particle size is about 6μm. By extending the ball milling time, the problem of coarse fly ash particles and uneven distribution is solved, which is conducive to the subsequent optimization of the rheological properties of the slurry, ensuring smooth shaping of dry and wet spinning and uniformity of the film structure after sintering.
[0052] like Figure 2 As shown, before modification: the oil rejection rate was low. After modification, Example 1 reached 95.2%, an increase of 31% compared to before modification, which is approximately 64.2% before modification. After modification, Example 2 reached 90.1%, an increase of 25.9%. After modification: the oil rejection rate was significantly increased to over 90%, with Example 1 reaching 95.2% and Example 2 reaching 90.1%. Moreover, the data showed high stability with no significant fluctuations. Polydopamine forms a modified layer on the membrane surface and within the pores. Through hydrophilic groups, hydroxyl and amino groups, water molecules are adsorbed. At the same time, the charged properties are used to repel oil droplets. The oil droplets in the oil-water emulsion are negatively charged, achieving efficient interception of oil droplets.
[0053] like Figure 3 As shown, before modification: the water flux is high; after modification: the water flux decreases slightly. The polydopamine modified liquid penetrates into the membrane pores through vacuum and spreads evenly by rotation, forming a thin modified layer on the surface of the ceramic membrane, resulting in a slight decrease in water flux.
[0054] Performance testing
[0055] The osmotic flux was determined using a self-made pressure osmosis apparatus in the laboratory. The osmotic flux (J, L·m) -2 ·h -1 The calculation formula is as follows: Where V is the permeate volume (L) over a certain period of time, and A is the effective membrane filtration area (m²). 2 ), where Δt is the test time (h).
[0056] The oil content in oil-water emulsions was analyzed using a UV-Vis spectrophotometer. The principle is based on the UV absorption characteristics of the -CH=CH- and -C6H5 groups in oils, and the fact that absorbance is directly proportional to the oil concentration in the solution. By plotting a standard curve and comparing the changes in absorbance before and after the standard curve, the oil content in the actual permeable side sample can be calculated, thus yielding the oil rejection rate. The oil rejection rate (R, %) is calculated using the following formula:
[0057] Cf and Cp are the oil concentrations (mg·L⁻¹) in the feed liquid and permeate, respectively. -1 ).
[0058] The calculated permeation flux is 18834 L·m⁻¹. -2 ·h -1 The oil rejection rate was 90.1%, which is 25.9% higher than that of the unmodified fly ash ceramic membrane, while maintaining a high permeation flux.
[0059] like Figure 4 As shown in af, Figure 4 a, Figure 4 d is a green blank with a rough surface and irregular gaps between particles. It is not sintered, the binder is not fully cured, there are many loose pores in the cross section, and the structural stability is poor. Figure 4 b、 Figure 4 e is the unmodified ceramic film. Due to sintering, the surface becomes relatively dense, sintering necks are formed between particles, the cross-section shows through channels, the porosity is >45%, but the pore walls are smooth without a modified layer, and the surface has insufficient hydrophilicity. Figure 4 c. Figure 4 f represents the modified ceramic membrane, with a thin and continuous polydopamine membrane uniformly covering its surface without localized accumulation. A uniform modified layer is visible on the inner wall of the cross-section channels, indicating that the channels are not blocked, thus verifying that the PDA is uniformly loaded within the membrane pores.
[0060] Gradient sintering reduces the accumulation of thermal stress and ensures the structural integrity of the support. Through three-stage temperature-controlled sintering, the loose green body is transformed into a support with a complete structure and interconnected channels, thus solving the problem of membrane cracking.
[0061] like Figure 5As shown, the water contact angle before modification was approximately 44.51°, which is a weakly hydrophilic or nearly hydrophobic state. This indicates that the surface of the unmodified fly ash ceramic membrane is not hydrophilic enough, which easily leads to oil droplet adhesion and contamination of the membrane surface. After modification, the water contact angle decreased to 26°, <30°, which is a strongly hydrophilic state. The hydrophilicity was significantly improved. The polydopamine modification layer introduced a large number of hydrophilic groups, hydroxyl groups, and -NH-, which reduced the contact angle between water and the membrane surface. This allowed the membrane surface to preferentially adsorb water molecules to form a water film, hindering the contact and adhesion of oil droplets to the membrane surface and reducing flux attenuation.
[0062] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, are covered within the scope of protection of the present invention.
Claims
1. A method for preparing a fly ash-polydopamine ceramic membrane for oil-water separation, characterized in that, Includes the following steps: S1 involves alkaline washing and acid washing of fly ash to obtain pretreated fly ash; S2 mixes the pretreated fly ash with polyvinylpyrrolidone (PVP), N-methylpyrrolidone (NMP) and polyethersulfone (PES) in a mass ratio of 60:2:80:20, adds distilled water, and then ball-mills the mixture in a planetary mill for 24 hours to obtain a slurry with a solid content of 50wt%. S3 The slurry is shaped by a wet-dry spinning device, and the shaped slurry is placed in an external exchange liquid for phase inversion to obtain a ceramic membrane fiber preform; the preform is then subjected to gradient sintering to obtain a fly ash ceramic membrane support. S4 The fly ash ceramic membrane support is vertically immersed in dopamine-modified alkaline solution, vacuumed for 10-20 minutes, and then transferred to a rotating device with a speed of 30 r / min for 10-15 minutes. The fly ash ceramic membrane support after S5 treatment was dried in a 55℃ constant temperature oven for 10-12 minutes to obtain polydopamine modified fly ash ceramic membrane.
2. The preparation method according to claim 1, characterized in that, The alkaline washing solution used is a 2-4 wt% sodium hydroxide solution or a 15-25 wt% sodium carbonate solution, and the solid-liquid ratio of the alkaline washing is 1 kg:1.5 L to 1 kg:3 L.
3. The preparation method according to claim 1, characterized in that, The pickling solution used is a 1-3 wt% citric acid solution, a 3-7 wt% hydrochloric acid solution, a 1-5 wt% sulfuric acid solution, or a 0.5-3 wt% nitric acid solution, with a solid-liquid ratio of 1 kg:0.5 L to 1 kg:2.5 L.
4. The preparation method according to claim 1, characterized in that, The molding pressure is set at 0.15 MPa, the inner core liquid is deionized water with a flow rate of 80 mL / min, the outer exchange liquid is anhydrous ethanol and deionized water in a volume ratio of 4:6, and the spinning pressure is 0.15 MPa.
5. The preparation method according to claim 1, characterized in that, The gradient sintering process includes three stages: Stage 1: 0℃-200℃, rate of 2-5℃ / min; holding time 80min; Stage 2: 200℃-600℃, rate of 2-5℃ / min; holding time 170min; Stage 3: 600℃-1100℃, rate of 3-5℃ / min; holding time 122min.
6. The preparation method according to claim 1, characterized in that, The dopamine-modified alkaline solution is based on Tris-HCl buffer solution, with the pH adjusted to 8.5-9, and dopamine hydrochloride is added to form the modified solution.
7. A fly ash-polydopamine ceramic membrane for oil-water separation, characterized in that, The ceramic membrane is prepared by any one of claims 1-6; the pore size of the ceramic membrane is 0.49 μm-2.24 μm.
Citation Information
Patent Citations
Fast and efficient boron removal hollow fiber composite membrane and preparation method thereof
CN106422809A
Preparation method of fly ash-based ceramic membrane support
CN115872772A